Public expenditures on education and health in Georgia before and during the global crisis - Maka Chitanava; Maya Grigolia; Lasha Labadze (Center for Social and Economic Research (CASE), 2011)
After years of stagnation and political cataclysms, Georgia tried to recover by launching radical economic and political reforms starting in 2004. The results of the reforms appeared to be impressive. The country's GDP has more than doubled; the total volume of bank deposits is five times what it used to be. Key international indices (Doing Business Index, Economic Freedom Index, Corruption Perception Index) have also reflected the success of the reforms. The occupation of the Georgian territories by Russia in August 2008 and the global financial crisis have significantly changed the current macroeconomic environment in Georgia. The August conflict undermined investor and consumer confidence, put pressure on public finances, damaged physical and other infrastructure and undermined the banking system with a large volume of deposit withdrawals. The deepening of the international financial crisis put further pressure on currency and foreign investments. The purpose of this paper is to consider the nature and magnitude of the impact of the global financial crisis on Georgia's social services sector and on the country's economy as a whole. The global financial crisis ahd a sharp impact on the most disadvantaged members of the society. The main objectives of the paper are to describe to what extent the education and healthcare sectors were affected in Georgia and to investigate how government policies have addressed the problems which arose due to the financial crisis.
Keywords: H11; H12; H51; H52; I11; I12; I18; I21; I22; I28; 330; Georgia; Education; Health Care Sector; Public Service Delivery; Development During the Financial Crisis; Financial Crisis in Georgia; Georgia's education sector; Georgia's health sector; Georgia's macro indicators; Financial aid; Öffentliche Finanzen; Öffentliche Ausgaben; Öffentliche Dienstleistung; Bildungswesen; Bildungsfinanzierung; Gesundheitswesen; Gesundheitskosten; Finanzkrise; Georgien